Kondisi sosial ekonomi pengelola ekowisata di Desa Loji Kecamatan Kulisusu Kabupaten Buton Utara - Aswan; La Ola, La Onu; Rosmawati; Sidiq, Azwar (Jurnal Sosial Ekonomi Perikanan, 2024)
This study alms to find out how the socio-economic conditions of mangrove ecotourism managers and to find out the amount of income for the managers of each business at a tourist object every month. This research was conducted in September-October 2020 in Loji village Kulisusu district North Buton Regency. Data were obtained through direct interviews with 15 respondents using a questionnaire. The data collected are age, education level, family dependents, health insurance, house conditions, transportation, social interaction, income from boar services and gazebo services. The data analysis used was descriptive qualitative and quantitative are analysis income, revenue, and total cost. The results of the study indicate that the social conditions of ecotourism managers in Loji village are that the existence of lourism objects provides benefits for the surrounding community while economically, the income obtained from the results of the ecotourism management business is IDR4,500,000 month